Electronic structure evolution from metallic vanadium to metallic VxOy: a nappes study for o2+v gas-solid interaction - Ranjan, Ravi; Mhamane, Nitin B.; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2022)
Gas-solid interactions between molecular oxygen and metallic vanadium surfaces and the systematic evolution in the electronic structure of vanadium oxide (VOx) surfaces have been explored in the present work by near-ambient pressure photo-electron spectroscopy (NAPPES). The current article studies the evolution of various oxides of vanadium as a function of partial pressure of O2 (ultrahigh vacuum to 1 mbar), temperature (298- 875 K), and the exposure time to oxygen (up to 18 h). Valence -band (VB) and core-level spectral measurements recorded with UV (He-I = 21.2 eV) and Al K alpha (1486.6 eV) photons, respectively, show interesting changes. (1) Oxidation is limited to the top layers of vanadium at 298 K and up to a partial pressure of 1 mbar O2. About 50% of vanadium gets oxidized, and the remaining amount exists as metal within the top 10 nm. (2) Metallic vanadium disappears above 625 K, and it is predominantly oxidized to a mixture of V4+ and V5+ oxidation states at a 0.1 mbar partial pressure of O2. Points 1 and 2 suggest the predominantly thermodynamically controlled nature of vanadium oxidation through oxygen diffusion into the subsurface and bulk layers. (3) The Fermi-level (EF) feature observed first at >= 725 K at a 0.1 mbar O2 pressure demonstrates the formation of metallic VO2; however, its metallic nature is preserved even at ambient temperature due to interweaving nanodomains of VOx with VO2. (4) Only partial conversion of surface layers to V5+ (V2O5) along with VO2 and V2O3 (within the probing depth of 8-10 nm by near-ambient pressure X-ray photoelectron spectroscopy (NAP-XPS)) was observed even after prolonged heating (18 h) in 1 mbar O2 pressure. (5) The nature of the surface changes between metal and semiconducting/ insulator oxides is substantiated by the observation of changes in work function (phi) and EF features. Typical VB features and Fermi intensity of V-metal and vanadium oxides were observed, and the results were corroborated with core-level and VB spectra. The present results extend the capabilities of NAPPES to explore the electronic structure evolution as a function of reaction conditions and underscore its relevance to areas such as heterogeneous catalysis and sensing.